97 Migration of the multicentre juvenile dermatomyositis cohort biomarker study and repository to REDCap. (23rd February 2023) - Hamilton, Roseanna; Wedderburn, Lucy; Sebire, Neil J; Spiridou, Anastassia; Varakliotis, Socrates; McCann, Liza; Martin, Neil; Papadopoulou, Charalampia
Abstract : Established in 2000, the Juvenile Dermatomyositis Cohort Biomarker Study and Repository (JDCBS) is a large cohort study of juvenile dermatomyositis (JDM) and related childhood onset inflammatory myositis conditions. The JDCBS has 17 centres around the United Kingdom contributing data and samples and supports multiple national and international studies in JDM and myositis. In this project, the study database was migrated to a new system and the data model was updated to align with an internationally agreed dataset for JDM. The new database was developed in REDCap, an electronic data capture software widely used in clinical research. Definition of the data dictionary was carried out iteratively through discussions with study clinicians, and comprised fields from the old database, all fields from the internationally agreed dataset, and a small number of entirely new fields. The REDCap database was tested by members of the study team at GOSH and a subset of the clinicians that sit on the JDCBS Steering Committee. Fields in the REDCap database were mapped to the corresponding fields in the old database and suitable software is being developed to automate the transfer of historic study data into REDCap. Following approval of all relevant contracts at each site, data entry to the old database will be frozen and all historic data migrated. Quality control checks of the data will be performed and all study team members given role-based access to REDCap to allow data collection to continue. Training on the new process and system has also been provided. This work demonstrates the complex migration of a long-running multicentre study to REDCap, including standardisation to an internationally agreed dataset for JDM. The migration will improve the usability, security, costs and maintainability of the database and collaborative research globally.